Effect of vitamin E on the quality of egg bonylip barb fish Osteochilus vittatus (Valenciennes, 1842) - Nurbety Tarigan; Ridwan Affandi; Firat Meiyasa (Syiah Kuala University, 2020)
Bonylip barb Osteochilus vittatus is a local fish species of significant economic value with vast potential in commercial freshwater fish culture. Traditional cultivation methods are currently employed depending on the seeds, although a low hatchery rate is assumed. The purpose of this study, therefore, was to determine the effect of dietary vitamin E on the quality of bonylip barb eggs, with the applied dosage of 0, 125, 250, and 375 mg/kg. Subsequent parameters measured include fecundity, drowned egg percentage, the chemical composition of eggs, and total energy retention. The results showed that several vitamin E doses significantly (P˂0.05) influenced these aforementioned constraints. Furthermore, the application of vitamin E at 375 mg/kg recorded the best dosage to improve egg quality. In addition, the fecundity was estimated at 23.484 grains, and sink egg percentage reached 92.66%, while protein and fat content were 21.43 mg/kg and 27.88%higher compared to the controlled sample. Therefore, It is concluded that the administration of vitamin E in the feed tends to increase egg quality of bonylip barb fish.